Amino Acid Oncometabolism and Immunomodulation of the Tumor Microenvironment in Lung Cancer - Fahrmann, Johannes F.; Vykoukal, Jody V.; Ostrin, Edwin J. (Frontiers in Oncology, 2020)
The observation that cancer acquires significant changes in its metabolism dates back nearly a century, to Otto Warburg noting that cancer cells preferentially utilize glycolysis even when there are not hypoxic conditions in the growth media. Altered energetics are thus considered a hallmark of cancer. However, it has become clear that altered metabolism is not limited to cellular energetic pathways. Alterations in amino acid synthesis and catabolism, lipid biogenesis, and other pathways such as polyamine processing are commonly seen in cancer. Additionally, alterations in metabolism do not only have profound effects for cancer cells, but also affect their surrounding microenvironment. With new cancer therapeutics targeting the immune microenvironment, these effects may have implications on cancer growth and response to therapy. These interactions are profound in lung cancer, further demonstrating the manifold interactions between developing tumors and the inflammatory microenvironment. Here, we discuss how dysregulation of metabolism in cancer alters its microenvironment and how this new-found knowledge can be exploited for anti-cancer treatment.